2021
DOI: 10.1002/joc.7137
|View full text |Cite
|
Sign up to set email alerts
|

Regional analysis of drought severity‐duration‐frequency and severity‐area‐frequency curves in the Godavari River Basin, India

Abstract: India is one of the most drought‐ravaged countries in the world and faces at least one drought in one region or another in every 3 years. There is no single reliable approach in characterizing future droughts. To understand future drought risk, potential changes of drought properties and characteristics are analysed in this study. Using Fuzzy c‐means clustering approach, homogeneous drought regions are identified in the Godavari river basin and therefore, optimum number of clusters were assigned as four. The 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Further, we detected a strong non-linear relationship between drought onset time and the deficit volume in monsoon-dominated catchments, which is often not assessed in earlier assessments. The methodology presented here and potential environmental controls can serve as a basis for climate change impact assessments and aid in multivariate frequency analysis of droughts, especially in regional contexts (Kumar et al, 2021), enhancing operational drought forecasts across river basins, especially in places where seasonality dominates streamflow variability. Our assessment emphasizes that environmental controls play a crucial role in understanding the severity of drought.…”
Section: Broader Implications Potential Transferability and Scope For...mentioning
confidence: 99%
“…Further, we detected a strong non-linear relationship between drought onset time and the deficit volume in monsoon-dominated catchments, which is often not assessed in earlier assessments. The methodology presented here and potential environmental controls can serve as a basis for climate change impact assessments and aid in multivariate frequency analysis of droughts, especially in regional contexts (Kumar et al, 2021), enhancing operational drought forecasts across river basins, especially in places where seasonality dominates streamflow variability. Our assessment emphasizes that environmental controls play a crucial role in understanding the severity of drought.…”
Section: Broader Implications Potential Transferability and Scope For...mentioning
confidence: 99%
“…However, the groundwater availability of the study area is rather uneven, with aquifers ranging from crystalline to sedimentary aquifers [1]. Moreover, due to the uneven distribution of rainfall because of climate change, groundwater usage has increased tenfold in different parts of the country [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that drought duration and occurrence are likely to increase for many regions in the future based on outputs from RCM/GCM (Touma et al ., 2015; Gu et al ., 2019; Huang and Fan, 2021). For instance, Kumar et al calculated 12‐month SPI index over the Godavari basin using MIROC‐ESM‐CHEM global climate model data for the three future simulations trying to understand future drought risk (Kumar et al ., 2021). They found that droughts in India may increase both in intensity and duration in the future.…”
Section: Introductionmentioning
confidence: 99%